Drug and Solvent Abuse Among Ahwaz\'s Elderlies - Abdolrahim Asadollahi (Sālmand, 2007)
Objectives: There are researches to point epidemiology of addiction to drugs, chemical and solvent abuse in elderlies. Drug and Solvent abuse is considered as one of these addictions. This study was point to chemical abuse among elderly population of Ahwaz an Iranian city during year of 2007.